Keberhasilan Transfer Pengetahuan dalam Suksesi Kepemimpinan melalui Pembelajaran Intergenerasional - Fransisca Desiana Pranatasari (Universitas Bunda Mulia, 2022)
Succession process of the next family business generation becomes an interesting phenomenon to be developed together with the process of adapting organizational knowledge. Organizational knowledge transfer is a difficult process in leadership succession. There are many factors that must be prepared in advance so that the business can achieve sustainability. This study uses a qualitative approach through in-depth interviews with several generations of successors in family businesses in Yogyakarta whose business scale is relatively the same. Triangulation of sources and member checks are carried out to ensure the validity of the data from this study. The result is that intergenerational learning has an important role in the succession process of family business leadership. Knowledge transfer in family business succession through intergenerational learning will facilitate the next generation in the process of adaptation to continue the previous leadership